Clamping force loss of high-strength bolts as a result of bolt head corrosion damage: Experimental research A. (January 2016) - Ahn, Jin-Hee; Lee, Jae Min; Cheung, Jin-Hwan; Kim, In-Tae
Abstract: In this study, the change in the clamping force of a high-strength bolt connection was quantitatively examined as a result of sectional damage of bolt head. High-strength bolt connection specimens were prepared, and the bolt heads were artificially damaged by handheld cutting tools. During the connection of the high-strength bolts and introduction of the sectional corrosion to the bolt heads, the change in the strain on the bolts was examined on the basis of the cutting depth of the handheld cutting tool and level of sectional damage of the bolt heads. Clamping forces of the bolts were shown to be affected by the cut depth of the handheld cutting tool. For larger sectional damage cases, greater reductions of the clamping force and greater variation in the strain reduction of the bolt were found. From the relationship between the clamping force loss and the corrosion damage of the bolt head, clamping force loss equations were suggested on the basis of the volume loss of the bolt head, diameter of the bolt head, and equivalent bolt diameter to estimate the re-clamping period or to determine when to exchange bolts for the maintenance work on steel structures. Highlights: Clamping force loss test for bolt connection depending on the corrosion damage of the bolt head Introducing artificial corrosion damage to bolt head from bolt head cutting Measuring change in the induced stress of the bolt depending on the artificial corrosion damage Examining relationship between clamping force loss of bolt and the corrosion damage of the bolt head